Pariwisata dalam Krisis: Investigasi Informasi Terkait Risiko, Persepsi Risiko, Kecemasan Perjalanan, dan Niat Perjalanan Wisatawan selama Pandemi COVID-19 - Novianti, Syifaa; Susanto, Eko; Widiyanti, Rikantini; Rafdinal, Wahyu (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
This study aims to determine: (1) the effect of risk-related information on risk perception; (2) the effect of risk perception on travel anxiety; (3) the effect of travel anxiety on travel intentions; (4) the effect of related information on travel intentions. The research used is descriptive analysis research with a quantitative approach and assisted by the SmartPLS program. Collecting data by distributing questionnaires with google form. The population in this study were all domestic tourists in Indonesia. The sampling technique used is accidental sampling. The sample is 403 respondents. The results showed that: (1) Information related to risk affects the perception of risk; (2) Perceived risk has a significant effect on travel anxiety; (3) Travel anxiety has a significant effect on travel intentions; (4) Information related to risk has a significant effect on travel intentions. Overall, risk-related information has an important role in influencing tourists' travel intentions. Thus, the role of risk-related information as an external factor becomes important in influencing the psychological factors of tourists during the COVID-19 pandemic. It is hoped that the government can make considerations in rebuilding tourism activities in Indonesia through policies that can support business people and protect the health of tourists and their communities. Keywords: Risk-Related Information, Risk Perception, Travel Anxiety and Travel Intention, Crises, COVID-19 Pandemics